PRODUCTION OF CUCUMBER SEEDLINGS IN ALTERNATIVE SUBSTRATES WITH DIFFERENT COMPOSITIONS OF AGRICULTURAL RESIDUES - Guisolfi, Louise Pinto (2018)
Studies on the use of agricultural residues as an alternative to commercial substrates have become fundamental tominimising the risk of environmental contamination resulting from inadequate disposal, as well as reducing seedling production costs. This research involved an evaluation of growth variables and quality of cucumber seedlings produced in substrates with different compositions of agricultural waste with a view to providing substitutes for commercial substrate. The experiment was based on a completely randomised design, with six treatments and ten replicates. There were five treatments with increasing proportions of moinha/decreasing proportions of carbonized rice husk (0/40, 10/30, 20/20, 30/10 and 40/0%) and fixed proportions of coconut fibre (15%), eggshell (5%), pine bark (40%), and one commercial substrate treatment as the control (Bioplant®). The variables evaluated were: electrical conductivity of the substrate, plant height, stem diameter, number of leaves, Dickson quality index (DQI) and dry matter of roots and above ground parts. Results show that alternative substrates can replace commercial substrate without impairing the quality of cucumber seedlings. However, the substrate containing 40% of moinha, 0% of rice husk, 15% of coconut fibre, 5% of eggshell and 40% of pine bark resulted in the highest values for all evaluated variables and appears to be the most promising alternative substrate for the production of cucumber seedlings.